The phenotype of bilateral hippocampal sclerosis and its management in "real life" clinical settings. (14th June 2018) - Sen, Arjune; Dugan, Patricia; Perucca, Piero; Costello, Daniel; Choi, Hyunmi; Bazil, Carl; Radtke, Rod; Andrade, Danielle; Depondt, Chantal; Heavin, Sinead; Adcock, Jane; Pickrell, W. Owen; et al.
Summary: Objective: There is little detailed phenotypic characterization of bilateral hippocampal sclerosis (HS). We therefore conducted a multicenter review of people with pharmacoresistant epilepsy and bilateral HS to better determine their clinical characteristics. Methods: Databases from 11 EPIGEN centers were searched. For identified cases, clinicians reviewed the medical notes, imaging, and electroencephalographic (EEG), video‐EEG, and neuropsychometric data. Data were irretrievably anonymized, and a single database was populated to capture all phenotypic information. These data were compared with phenotyped cases of unilateral HS from the same centers. Results: In total, 96 patients with pharmacoresistant epilepsy and bilateral HS were identified (43 female, 53 male; age range = 8‐80 years). Twenty‐five percent had experienced febrile convulsions, and 27% of patients had experienced status epilepticus. The mean number of previously tried antiepileptic drugs was 5.32, and the average number of currently prescribed medications was 2.99; 44.8% of patients had cognitive difficulties, and 47.9% had psychiatric comorbidity; 35.4% (34/96) of patients continued with long‐term medical therapy alone, another 4 being seizure‐free on medication. Sixteen patients proceeded to, or were awaiting, neurostimulation, and 11 underwent surgical resection. One patient was rendered seizure‐free postresection, with an improvement in seizures for 3 other cases. By comparison, of 201 patients with unilateral HS, a significantly higher number (44.3%) had febrile convulsions and only 11.4% had experienced status epilepticus. Importantly, 41.8% (84/201) of patients with unilateral HS had focal aware seizures, whereas such seizures were less frequently observed in people with bilateral HS, and were never observed exclusively ( P  = .002; Fisher's exact test). Significance: The current work describes the phenotypic spectrum of people with pharmacoresistant epilepsy and bilateral HS, highlights salient clinical differences from patients with unilateral HS, and provides a large platform from which to develop further studies, both epidemiological and genomic, to better understand etiopathogenesis and optimal treatment regimes in this condition.